Identification of common problems faced by the Bumiputera contractors / Ad. Johan Abdullah - Abdullah, Ad.Johan (Faculty of Civil Engineering, 2006)
This thesis studies the identification of common problems faced by Bumiputera contractors in Perlis and Pulau Pinang. The data collections were used to explain level of the common problems by the contractors, the difference between contactor’s demographic factors toward common problems. The samples consist of 50 contractors in Perlis and Pulau Pinang, then the data was collected using self-administered questionnaire. For the analyses One-way ANOVA were used in this study. The result indicated that the level of the common problems faced by Bumiputera contractors in Perlis and Pulau Pinang is low. However, contractors in F class tend to face with the common problems compared with the contractors in A class. The common problems have simplified into the unique problems which is consist of the financial, procedures, human resources, management and the others problems. There was no difference in unique problems between the respondents joined the company (in Year).The interesting finding in this study because it can be determined the problems rank due to the frequency of the problems faced. Therefore, the common problems faced by the Bumiputera contractors in Perlis and Pulau Pinang are not very seriously but its can bring negative effect to their company performance. The finding of this study about the common problems faced by Bumiputera contractors can be useful and make it as guidance for the other researchers in the future. This study also provides suggestions and recommendations for future research.